2010
DOI: 10.1589/jpts.22.419
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Age-Associated Changes of Gait and Falls and Life-Space in Elderly People

Abstract: Abstract.[Purpose] The aim of this study was to identify the age-associated changes in gait speed, stride length, cadence and step width, and to examine the relationship between these gait variables with a history of falls and life-space experience among elderly people.[Subjects] The participants were 848 healthy elderly adults (mean age 80 years, range 73-91, 76.8% women) living independently at home. [Methods] Gait speed, stride length, cadence and step width were measured at a normal pace using WalkWay, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 36 publications
3
47
0
2
Order By: Relevance
“…In contrast, Shimada et al . carried out a study with 848 older people for 5 years, and found a strong association between risk of falls and decreased gait speed and fast cadence . However, these studies evaluated falls among older people without taking frailty into account.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Shimada et al . carried out a study with 848 older people for 5 years, and found a strong association between risk of falls and decreased gait speed and fast cadence . However, these studies evaluated falls among older people without taking frailty into account.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the previous study has shown that the walking energy cost for a comparable speed is generally higher for healthy and mobility, and that diminished pulmonary function is associated with declining physical function [20]. Malatesta et al reported that healthy octogenarians exhibited higher walking cost and greater stride time variability [21] and also reported that these declines in physical performances were apparent at age 80 years and over in women and at age 90 years and over in men [13]. Shimada reported that increased VO 2 in older adults manifests as walking becomes inefficient and reduced endurance capacity occurs [22].…”
Section: Relationship Between Walking Efficiency and Life-space Assesmentioning
confidence: 97%
“…Murata et al reported that life space was related not only to age or health status but also to environmental or psychosocial factors [12]. Shimada et al's reports confirm that LSA was more strongly associated with gait speed than the other gait variables [13] and also show that these declines in physical performances were apparent at age 80 years and over in women and at age 90 years and over in men [13].…”
Section: Life-space Assessmentmentioning
confidence: 98%
See 2 more Smart Citations